THE STATE ROAD NETWORK AS A FACTOR OF SPATIAL INTEGRATION OF SERBIAN COMMUNITIES IN KOSOVO AND METOHIJA: GIS ANALYSIS - Ristić, Dušan (Bulletin of Natural Sciences Research, 2026)
Following the armed conflicts in Kosovo and Metohija at the end of the twentieth century and the establishment of the United Nations Mission administration, a large number of members of the Serbian population were displaced, resulting in significant changes in their spatial distribution. In the twenty-first century, Serbs in Kosovo and Metohija predominantly reside in a limited number of municipalities with a Serbian majority or a pronounced Serbian population, as well as in spatially isolated enclaves comprising individual settlements or clusters of smaller settlements. These areas are characterized by complex living and security conditions, as well as pronounced spatial isolation. Given their demographic fragmentation, spatial dispersion, and dependence on institutional, educational, healthcare, and service centers, transport connectivity represents one of the key factors of the spatial and functional integration of the Serbian population. The aim of this paper is to determine, through the application of GIS analysis, the relationship between the state road network and the areas in which the Serbian population has persisted, as well as to assess their level of accessibility in relation to the main Serbian centers. The study employed isochrone and isotel accessibility models derived from the state road network. The analysis reveals a strong correspondence between the routes of state roads and the areas inhabited by Serbian communities and enclaves. The findings confirm that the state road network in Kosovo and Metohija serves as an important integrative factor in maintaining spatial connectivity and supporting the everyday functioning of Serbian communities, while also showing that physical proximity to road corridors alone is not sufficient without adequate travel-time and spatial accessibility to the main Serbian centers.